STATE DEFENSE EDUCATION AS A COURSE IN UNIVERSITY - Indrawan, Jerry; Aji, M. Prakoso (Indonesia Defense University, 2018)
Indonesia currently faces multidimensional threats, from small to large, concerning all aspects of the country's life, from ideology, politics, economics, social, culture, defense, and security. The nature of contemporary threat has a human security aspect rather than only state security. As such, a thorough effort is needed to deal with those Threats, Disruption, Obstacle, Challenge (TDOC). State defense can be the answer to such problems because state defense itself can be interpreted as an obligation and responsibility of citizens to maintain the existence and sovereignty of the state. State defense will be optimal if disseminated through formal education. In this case, the formal education in question is at the level of higher education. This paper proposes that state defense can be held at higher education level in the form of university compulsory course, and is organized under the name State Defense Education. This State Defense Education is not military education or conscription, but an education that is adjusted to the condition and nuance of higher education.Keywords: Threat, Human Security, State Defense, and State Defense Education